Good Hospital Governance at the Indonesian Hospital - Tjaija, Abunawas; Sabir, Muhammad; Usman, Munawir H.; Samad, Muhammad Ahsan (International Journal of Criminology and Sociology, 2021)
This study aims to describe the commitment of stakeholders in implementing the Good Hospital Governance policy at the Undata Regional General Hospital, Central Sulawesi Province, Indonesia. The method used is a qualitative exploratory approach with 13 (thirteen) informants who were determined by purposive sampling, the data analysis used was an interactive model data analysis from Miles and Huberman by triangulating methods and data sources. The results showed that the successful implementation of the Good Hospital Governance policy at Undata Hospital, Central Sulawesi Province which was viewed from 6 (six) supporting aspects of the implementation of the Van Metter and Van Horn policies had not been running properly. That is; aspects of resources, aspects of the characteristics of the executing agent, aspects of the attitudes/tendencies (dispositions) of the executing agents, and aspects of the external environment (economic, social, and political). Besides, an implementation must also be supported by the commitment of the owner, board of directors, and management as well as all hospital staff, to implement the principles of transparency, accountability, independence, responsibility, equality, and fairness.